How to Assure That Farmers Apply New Technology According to Good Agricultural Practice: Lessons From Dutch Initiatives - Lotz, Lambertus A. P.; van de Wiel, Clemens C. M.; Smulders, Marinus J. M. (Frontiers in Environmental Science, 2018)
The application of Good Agricultural Practice (GAP) contributes to many aspects of sustainable farming, including integrated control of weeds, diseases and pests and optimisation of fertilization and irrigation. It is a relatively neglected issue in debates around the application of new technology, such as genetic modification (GM), which often revolve around intrinsic properties of a GM crop allegedly leading to unsatisfactory performance. However, the performance largely depends on agronomic and institutional embedding of applying new technology, which generally applies to all crops, whether conventional or GM. We describe and discuss four cases in which the government or private partners in the production chain regulate this, using legal measures, incentives, or mutual agreements, or a combination thereof. These cases serve as a starting point for a discussion on how GAP can be stimulated, organized and guaranteed. We argue that next to the government, seed suppliers, ngo’s and buyers, also farmers can be drivers for the application of GAP when tools are developed that enable them to make optimal farming choices.